Parasitemia and antibody response to benznidazole treatment in a cohort of patients with chronic Chagas disease - Moreira, Carlos Henrique Valente; Bierrenbach, Ana Luiza; Taconeli, Cesar Augusto; de Oliveira-da Silva, Léa Campos; Buss, Lewis F.; Keating, Sheila M.; Manuli, Erika Regina; Carvalho, Noemia Barbosa; Guastini, Cristina; Coco, Sonia Bakkour; Lindoso, José Ângelo Lauletta; Franco, Lucas Augusto Moyses; et al. (Frontiers in Parasitology, 2023)
Background Evaluating the effectiveness of Chagas disease treatment poses challenges due to the lack of biomarkers for disease progression and therapeutic response. In this study, we aimed to assess the clearance of Trypanosoma cruzi (T. cruzi) parasites in a group of benznidazole (BNZ)-treated chronic Chagas disease patients using high-sensitivity quantitative PCR (qPCR) and track T. cruzi antibody levels through a semiquantitative chemiluminescent assay. Methods A total of 102 T. cruzi seropositive patients with previous PCR-positive results were enrolled in the study. We collected samples 30 days before treatment (T-30d), on the day before initiating BNZ treatment (T0d), and at follow-up visits 60 days (T60d), 6 months (T6M), 12 months (T12M), and 36 months (T36M) after treatment initiation. Treatment efficacy was assessed by testing of serial samples using a target-capture qPCR assay specific to satellite T. cruzi DNA and the ORTHO T. cruzi ELISA Test System for antibody quantitation. Results Of the enrolled individuals, 87 completed at least 50% of the treatment course, and 86 had PCR results at follow-up visits T6M, T12M, and T36M. PCR results exhibited fluctuations before and after treatment, but levels were significantly lower post-treatment. Only 15 cases consistently tested PCR-negative across all post-treatment visits. Notably, nearly all participants demonstrated a declining antibody trajectory, with patients who tested PCR-negative at T36M exhibiting an earlier and more pronounced decline compared to PCR-positive cases at the same visit. Conclusion Our study suggests that serial PCR results pose challenges in interpretation. In contrast, serial antibody levels may serve as an ancillary, or even a more reliable indicator of parasite decline following BNZ treatment. Monitoring antibody levels can provide valuable insights into the efficacy of treatment and the persistence of parasites in Chagas disease patients.